2021
DOI: 10.1177/11206721211020203
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of intravitreal Fluocinolone Acetonide microimplant (ILUVIEN®) in patients with chronic diabetic macular edema: 1 year follow-up

Abstract: Purpose: Evaluate the efficacy and safety of intravitreal 0.19 mg fluocinolone acetonide (FAc) micro implant in patients with chronic diabetic macular edema (cDME). Methods: Prospective study recruiting subjects with cDME. Inclusion criteria: cDME for at least 2 years documented with OCT imaging; pseudophakia; previous treatments with laser photocoagulation and intravitreal injections of anti-VEGF and/or dexamethasone. Exclusion criteria: phakia; ocular hypertension; tractional component visible on OCT; glauco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(30 reference statements)
0
6
1
Order By: Relevance
“…Moreover, other real-life studies provided lower visual outcomes, with BCVA gains ranging from + 3.8 to 5.0 letters after 12 months (25). In our study, the long-standing course of the chronic DME in association with the multiple injections before FAc implant may have led to a higher percentage of disorganization of the inner retinal layer (DRIL) in comparison with previous studies, in which an early-switch to Fac has been performed (15). In this regard, it is known that the presence of DRIL is predictive for visual function recovery (26).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Moreover, other real-life studies provided lower visual outcomes, with BCVA gains ranging from + 3.8 to 5.0 letters after 12 months (25). In our study, the long-standing course of the chronic DME in association with the multiple injections before FAc implant may have led to a higher percentage of disorganization of the inner retinal layer (DRIL) in comparison with previous studies, in which an early-switch to Fac has been performed (15). In this regard, it is known that the presence of DRIL is predictive for visual function recovery (26).…”
Section: Discussioncontrasting
confidence: 60%
“…FAc implant has the clinical indication for the management of visual loss due to chronic/relapsing DME, which is insu ciently responsive to other rst-line available therapies (11). After the pivotal FAME trial, other real-life studies provided promising results about FAc clinical e cacy and safety pro le (12)(13)(14)(15)(16)(17)(18); however, despite the encouraging results documented, there is still need of further real-life evidence of Fac clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-VEGF drugs have been widely used in ocular diseases such as exudative age-related macular degeneration, diabetic macular edema, choroidal neovascularization, and RVO-ME, and have shown good safety and efficacy. Previous retrospective and prospective studies have shown that the anti-VEGF treatment for RVO-ME in real-word has achieved significant retinal structure improvement and visual function recovery ( 5 , 17 , 29 , 33 , 37 , 38 ). The patients included in this study are divided into the mAb group (ranibizumab injection) and the Fc group (injection of conbercept or aflibercept) according to their mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…has achieved significant retinal structure improvement and visual function recovery (5,17,29,33,37,38). The patients included in this study are divided into the mAb group (ranibizumab injection) and the Fc group (injection of conbercept or aflibercept) according to their mechanism of action.…”
Section: ) (E)mentioning
confidence: 99%
See 1 more Smart Citation